PENGARUH EDUKASI EKONOMI KELUARGA, LINGKUNGAN KELOMPOK SEBAYA TERHADAP NIAT KEWIRAUSAHAAN DENGAN MEDIASI LITERASI EKONOMI PADA MAHASISWA UNIVERSITAS PELITA HARAPAN KARAWACI - Laynardi, Erianto Imannuel; Budiono, Sidik (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2024)
The increasing development of the unemployed mainly occurs due to the imbalance of available job vacancies compared to job applicants. Entrepreneurship could be one of the solutions to the job vacancies and job applicant imbalance. Proper knowledge is required to understand factors that could affect the entrepreneurial intentions of college students. The purpose of this research is to see the influence of factors that can influence Entrepreneurial Intentions, such as Family Economic Education, Peer Groups, And Economic Literacy.  The research uses quantitative research with data collection techniques using surveys distributed via Google Form and processed using the SEM AMOS and SPSS programs. The research collected 250 samples, namely students who met the specified conditions. The study results show that: 1) Family Economic Education has a positive and significant effect on Entrepreneurial Intentions. 2) Family Economic Education has a positive and significant effect on Economic Literacy. 3) The Peer Group Environment influences Entrepreneurial Intentions positively and significantly. 4) The Peer Group Environment has a positive and significant effect on Economic Literacy. 5) Economic Literacy influences Entrepreneurial Intentions positively and significantly. Through this, the results show that parents have an important role in building entrepreneurial intentions and educational institutions need to consider utilizing learning programs to promote learning through peer groups to build entrepreneurial intentions